Motivation of Online Merchant Students (Case Study of 5 Online Shop Seller Students at Makasar State University) - Ramli, Mauliadi (Universitas Negeri Makassar, 2023)
This research aims to find out: 1) What is the motivation for students to become online shop sellers? 2) What is the impact felt by students who sell online shops. This type of research is descriptive qualitative research with a qualitative approach. The selection of informants used a purposive sampling technique with a total of 5 informants. The criteria for informants were selected and adjusted to research needs so that researchers could find out the motivation and impact of online shop sellers. The data collection techniques used are: Observation, interviews and documentation. The data obtained was then analyzed using descriptive quantitative through three stages, namely data reduction, data presentation, and drawing conclusions.The results of this research show that based on the motivation of students selling online shops at Makassar State University, it is because they want to help their parents, to earn additional income. By using this online shop, sellers don't have to bother going to the shop to get the goods they want. To make a transaction, both parties don't need to meet each other. Once buyers select a product, they can pay for it with a credit or bank card, and the product will be shipped to the buyer's desired location. The positive impact felt by online shop sellers is that they can make their own money, their time is more useful and they can meet lots of people when delivering their products to people, they can also introduce their products outside the area. There is also a negative impact felt by online shop sellers, namely that they often suffer losses because Many people cancel (return) olnine shope marketplace via COD.